Jejak Sunyi Menuju Api Biru Menyusuri Alam dan Makna di Kawah Ijen - Mochammad Amboro Alfianto; Lady Khania Cahya Ramadhina Sihotang; Najwa Falma Nurvea; Azmi Farid Hasan; Eka Awfa Nasywa; Darrel Zahran Mardhan (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to describe and analyze the natural landscape of Banyuwangi as experienced on the journey to Ijen Crater. Using a descriptive qualitative approach, this study records the physical, ecological, social, and emotional transformation of the landscape through direct observation, visual documentation, and reflective narratives. Ijen Crater as a natural tourism destination not only presents geological phenomena such as blue fire and acid lakes, but also represents a mosaic of landscapes that include agricultural zones, montane forests, community activities, and tourism dynamics. The findings show that the journey to Ijen Crater shows the complexity of landscape elements, the involvement of local communities in managing the space, and the appreciation of tourists that form personal and spiritual meanings. The conclusion of this study is that the journey is not just a physical movement, but a means to understand the relationship between humans and living nature. The implications of this study underline the importance of participatory and sustainable landscape-based ecotourism management.